The Relationship Between Mental Health and Mental Toughness with Meaning in Life in Families of Children with Autism - Mahdi Zadeh Tourzani, Melika; Azizi, Mohammad Parsa; Hakimi Rad, Elham (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present study aimed to determine the relationship between mental health and mental toughness with the meaning in life in families of children with autism.Methods: The statistical population included all families with children with autism registered in the Autism Society of Tehran in 2022 (totaling 2,040 individuals). From this population, 322 participants were selected using convenience sampling based on Morgan's table. Participants were assessed using the General Health Questionnaire (GHQ) by Goldberg (1999), the Mental Toughness Questionnaire by Clough, Earle, and Sewell (2002), and the Meaning in Life Questionnaire by Steger, Frazier, Oishi, and Kaler (2006). Data were analyzed using Pearson’s correlation coefficient and multiple regression tests via SPSS version 23.Findings: The findings revealed a significant relationship between meaning in life and both mental health and mental toughness in families of children with autism. The dimensions of mental health significantly predicted the presence of meaning and the search for meaning in life. Furthermore, the dimensions of mental toughness were also significant predictors of the presence of meaning and the search for meaning (P < 0.001).Conclusion: Based on the results, the role of mental health and mental toughness is crucial in fostering a positive experience of meaning in life for families of children with autism.